x 3(x 2 + 5x + 1)
x6+ 5x4+x3
x5+ 5x4+x3
x5+ 5x3+x3

Question

Asked 3/5/2013 9:16:30 AM

Updated 6/26/2014 12:50:10 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/26/2014 12:50:08 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

bongche|Points 3864|

shiela098|Points 205|

lechatelier|Points 86|

hatuti|Points 354|

Question

Asked 3/5/2013 9:16:30 AM

Updated 6/26/2014 12:50:10 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/26/2014 12:50:08 AM]

Rating

8

(y + z)^3 = y^3+ 3y^2z+ 3yz^2+z^3

Added 6/26/2014 12:30:57 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:43:51 AM]

8

(6 - d)(d2 - 5 + 3d) = -d3+ 3d2+ 23d- 30

Added 6/26/2014 12:50:10 AM

This answer has been confirmed as correct and helpful.

Solve for x.
5x - 6 = 4x + 8
**Weegy:** x=-0.91 is the answer. **User:** If $400 is invested at the rate of 6% for one year, what will be the total value of the investment (the amount)?
**Weegy:** First calculate the simple interes. I=prt = 400*.06*1 = 24. Then add the interest to the principle. 400+24=424. The total value of the investment will be $424. (More)

Question

Expert Answered

Asked 3/4/2013 12:11:43 PM

0 Answers/Comments

15% of $75
**Weegy:** Hello, How are you , can I answer a question for you ? **User:** WHAT IS 15% OF $75! **Weegy:** Hello, How are you , can I answer a question for you ? (More)

Question

Updated 11/27/2014 5:32:37 AM

1 Answer/Comment

15% of 75 is 11.25

.15 x 75 = 11.25

.15 x 75 = 11.25

Added 11/27/2014 5:32:36 AM

This answer has been confirmed as correct and helpful.

-7(8 + k)
-56 + 7k
-7k - 56
-7k + 56 **Weegy:** -7(8 + k) = -7k - 56 **User:** Simplify 7(n - p) + 5p.
-7n - 12p
7n - 12p
7n - 2p **Weegy:** 7(n - p) + 5p
= 7n - 2p **User:** Simplify 8y(y - 4) + 3y(y + 2).
24y2- 26y,
11y2- 26y- 8,
11y2- 26y,
11y2- 8, **Weegy:** 8y(y - 4) + 3y(y + 2) = 11y^2 - 26y
Solution:
8y(y - 4) + 3y(y + 2)
= 8y^2 - 32y + 3y^2 + 6y
= 11y^2 - 26y **User:** Simplify p(p - q) - q(q - p).
p2-q2
p2+q2
p2+pq-q2
p2-pq-q2 **Weegy:** p(p - q) - q(q - p) = p2 - q2 **User:** Find the product.
-2xa(-4xb - 2x 3 + 5x)
-8xa+b- 4xa+3- 10xa+1
8xa+b+ 4x3a- 10xa
8xa+b+ 4xa+3- 10xa+1 (More)

Question

Not Answered

Updated 7/9/2014 10:41:00 AM

0 Answers/Comments

Simplify the given equation.
17x - 6 + 3x - 5 = x + 11 + 4x
20x - 11 = 5x + 11
20x + 1 = 5x + 11
9x = 16x **Weegy:** 20x-11=5x+11 **User:** Solve for x.
7x + 9 = 6x - 5
**Weegy:** 5x - 6 = 4x + 8, 5x - 4x = 8 + 6, x = 14 **User:** Solve for x.
5x - 6 = 4x + 8
(More)

Question

Updated 5/28/2014 10:52:30 PM

2 Answers/Comments

7x + 9 = 6x - 5

7x - 6x = -5 - 9

x = -14

7x - 6x = -5 - 9

x = -14

Added 5/28/2014 10:52:08 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/28/2014 10:54:54 PM]

5x - 6 = 4x + 8

5x - 4x = 8 + 6

x = 14

5x - 4x = 8 + 6

x = 14

Added 5/28/2014 10:52:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/28/2014 10:55:31 PM]

Simplify (8z - 10) ÷ (-2) + 5(z - 1).
z
z - 1
z - 2
**Weegy:** 2(4z-5)/-7+5z This is the simplified form. (More)

Question

Updated 3/6/2013 6:11:32 AM

1 Answer/Comment

(8z - 10) ÷ (-2) + 5(z - 1)

= 5 - 4z + 5z - 5

= z

= 5 - 4z + 5z - 5

= z

Added 3/6/2013 6:11:32 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/21/2014 1:58:11 PM], Rated good by andrewpallarca

39,061,951

questions answered

There are no comments.